Temperament and Character in Mood Disorders: Influence of DRD4, SERTPR, TPH and MAO-A Polymorphisms - Serretti, Alessandro; Mandelli, Laura; Lorenzi, Cristina; Landoni, Samuela; Calati, Raffaella; Insacco, Chiara; Cloninger, C. Robert (Neuropsychobiology, 2006)
Abstract Gene variants exert a complex range of effects on human normal and abnormal behavior. We previously reported the effect of gene variants in serotoninergic and dopaminergic pathways, in a range of clinical features in mood disorders, such as symptomathology, periodicity, social adjustment and treatment response. In this paper we hypothesized that the same gene variants could influence temperamental traits in mood disorders patients. We focused on genes of the serotoninergic and dopaminergic systems (dopamine receptor D4 gene, DRD4; serotonin transporter gene, promoter region SERTPR; tryptophan hydroxylase gene, TPH; monoamine oxidase A gene, MAO-A). Two hundred and seven euthymic subjects, affected by major depressive disorder (n = 73) and bipolar disorder (n = 134) were assessed by the Cloninger’s Temperament and Character Inventory (TCI) and typed using PCR-based analyses. Possible stratification factors such as demographic, clinical and other temperamental factors were also taken into account. We observed that homozygosity for the short SERTPR allele was associated with low novelty-seeking scores (p = 0.006) and genotypes containing the DRD4 long allele were marginally associated with low harm avoidance (p = 0.05). Finally, the long MAO-A allele was associated with decreased persistence scores among females (p = 0.006). Our observation of a pattern of influence on temperamental dimension exerted by serotonergic and dopaminergic genes suggests that the contribution of these polymorphisms to the clinical presentation of mood disorders could be mediated by an influence on personality differences.